Computational network pharmacology and virtual screening analysis of chemical constituents of plants used in the traditional drink "Al-Jur" against COVID-19 and seasonal respiratory diseases - Tahri, Aida, Auteur; Tifouri, Nadjoua; Boufissiou, Ahmed; Boubrima, Youcef (Laghouat : Université Amar Telidji - Département de biologie, 2025)
This study combines computational network pharmacology and virtual screening to evaluate the therapeutic potential of the traditional multi-herb beverage "Al-Jur" against COVID-19 and other respiratory infections. Traditionally used to treat respiratory and digestive disorders, "Al-Jur" is analyzed here for its key bioactive compounds and their pharmacological interactions. Using systems-level pharmacology tools, interactions between phytochemicals and disease- related protein targets were mapped, with particular focus on COVID-19 and other respiratory pathogens. In parallel, bioactive compounds were virtually screened against these targets to assess binding affinities and potential inhibitory effects. Results suggest that the compounds from "Al-Jur" act on a network of functionally related proteins, influencing entire biological pathways rather than single molecular targets. These findings support the potential of this traditional remedy as a multi-target therapeutic candidate for managing respiratory infections, including COVID-19.